PENGARUH PEMBELAJARAN PENDIDIKAN PANCASILA PADA MATERI PENERAPAN NILAI-NILAI PANCASILA TERHADAP KESADARAN MENAATI TATA TERTIB SEKOLAH PADA SISWA (Studi Korelasi di SMPN 1 Angsana) - Fetrianti, Yuli; Dewi, Ratna Sari; Fitrayadi, Dinar Sugiana (UNTIRTA CIVIC EDUCATION JOURNAL, 2023)
This research has the aim to determine the effect of pancasila education learning on students' awareness of conform school rules at SMP Negeri 1 Angsana. Identification of problems shows that there are some problems, such as the existence of students who are not yet aware of the importance to conform the rules, weak awareness of school rules and differences in interest levels and motivation to learn which influence the level of student discipline. This research uses a quantitative approach with a correlational method to see the correlation between the relationship Pancasila Education learning variable (variable X) and awareness of obeying school rules (variable Y). The results show that learning Pancasila education has a significant influence on awareness of conform school rules, with a significance value of  0,001 which is smaller than 0,05, as well as the tcount value 4,175 which is greater than ttable 1,665. The correlation test shows that there is a moderate relationship with the correlation value 0,437. Based on the results that have been presented, it can be concluded that learning Pancasila education has a significant effect on students' awareness. This research provides important implications in strengthening Pancasila education learning as an effort to improvement students' awareness of discipline in schools.